2009
DOI: 10.1017/s1368980009990747
|View full text |Cite
|
Sign up to set email alerts
|

An ecological analysis of factors associated with food insecurity in South Australia, 2002–7

Abstract: Objective: To estimate the extent of food insecurity in South Australia and its relationship with a variety of socio-economic variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
3
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 29 publications
6
81
3
5
Order By: Relevance
“…In the ecological study conducted by Foley et al 23 in South Australia with 19,037 individuals, a significant association was also found between low education level and food insecurity (p<0.01). A study in Canada also found that workers with low education level were significantly more likely to be food insecure 18 .…”
Section: Discussionmentioning
confidence: 82%
“…In the ecological study conducted by Foley et al 23 in South Australia with 19,037 individuals, a significant association was also found between low education level and food insecurity (p<0.01). A study in Canada also found that workers with low education level were significantly more likely to be food insecure 18 .…”
Section: Discussionmentioning
confidence: 82%
“…In terms of characteristics of the target populations studied, seven of the eighteen studies examined adults of varying ages (37)(38)(39)(43)(44)(45)(46) , seven explicitly examined families with children (sometimes with data collected using the child as the sampling unit) (40,42,(47)(48)(49)(50)(51) , three focused on seniors (41,52,53) , and one sampled a range of ages (children and adults) (54) . Seven out of the eighteen studies (39 %) focused exclusively on low-income or ethnic subgroups (39,44,46,(48)(49)(50)(51) .…”
Section: Literature Search and General Overviewmentioning
confidence: 99%
“…Five studies used the six-item short form of the USDA Food Security Scale (37)(38)(39)42,47) , three studies used items from the Community Childhood Hunger Identification Project in the National Health and Nutrition Examination (NHANES) III surveys (46,50,53) , and one study was based on items administered in the Behavioral Risk Factor Surveillance System (41) . The three Australian studies (45,52,54) and Dean and Sharkey (2011) (43) adapted and used items from the Radimer/Cornell measure, while Sharkey et al (2011) used an adapted version of the complete Radimer/Cornell measure (49) . Eight studies investigated different types or degrees of severity of food insecurity, by using either more than one questionnaire item or different thresholds for the USDA eighteen-item Food Security Scale or the Radimer/Cornell Scale (41,(43)(44)(45)(48)(49)(50)(51) .…”
Section: Literature Search and General Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from developed nations show that low income is clearly one of the most important determinants of FI (9)(10)(11)(12) , although many food-insecure households are not in poverty (9) . Other demographic and socio-economic factors are associated with an increased risk of FI: single-parent families, the presence of young children and housing conditions (e.g.…”
mentioning
confidence: 99%